Putusan Mahkamah Konstitusi Terkait Kewenangan PPNS dalam Penyidikan TPPU dan Implikasinya Terhadap Penegakan Hukum - Prianter Jaya Hairi (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
The decision of the Constitutional Court Number 15/PUU-XIX/2021 states the phrase in the Elucidation of Article 74 of the Law on the Prevention and Eradication of the Crime of Money Laundering (PECML) as conditionally constitutional. The explanation interprets the phrase “predicate criminal investigators”, which must be interpreted as “an official or agency that is authorized by laws and regulations to carry out investigations”. This article examines the Constitutional Court’s considerations in interpreting the Elucidation of Article 74 of the PECML Law and its implications for law enforcement of crime of money laundering (CML). In addition, this article is expected to offer some viewpoints regarding the preparedness of Civil Servant Investigators (CSI) in carrying out the authority to investigate money laundering offenses. This article is empirical-normative legal research, with qualitative data analysis methods. The discussion analize that the formulation of the explanation of Article 74 of the PECML Law has indeed led to norms ambiguity, namely that there is an inconsistency between the Elucidation of Article 74 and the provisions of the main norm, this is also one of the conditionally constitutional considerations by the Constitutional Court. In addition, the Constitutional Court’s decision has implications for the opening of the faucet of CML law enforcement which has now become a multi-investigator. The duties and authorities of CML investigations regulated in the PECML Law are now also given to all predicate criminal investigators (including CSI). This article recommends that CSI improvements need to be continuously pursued so that the quantity, quality, and professionalism of CSI continue to increase so that they can carry out the function of CML law enforcement effectively. AbstrakPutusan Mahkamah Konstitusi Nomor 15/PUU-XIX/2021 menyatakan frasa pada Penjelasan Pasal 74 UU PPTPPU sebagai konstitusional bersyarat. Penjelasan tersebut menafsirkan frasa “penyidik tindak pidana asal”, harus dimaknai sebagai “pejabat atau instansi yang oleh peraturan perundang-undangan diberi kewenangan untuk melakukan penyidikan”. Artikel ini mengkaji pertimbangan Mahkamah Konstitusi dalam menafsirkan Penjelasan Pasal 74 UU PPTPPU, dan implikasinya terhadap penegakan hukum TPPU. Selain itu, artikel ini diharapkan dapat memberi masukan terkait kesiapan PPNS dalam mengemban wewenang penyidikan TPPU. Artikel ini merupakan penelitian hukum empiris-normatif, dengan metode analisis data yang bersifat kualitatif. Hasil pembahasan bahwa perumusan terhadap penjelasan Pasal 74 UU PPTPPU memang telah menimbulkan ketidakjelasan norma, yaitu terjadi ketidakselarasan antara Penjelasan Pasal 74 dengan ketentuan norma pokoknya, hal itu pula yang menjadi salah satu pertimbangan konstitusional bersyarat oleh MK. Selain itu, Putusan MK berimplikasi pada terbukanya keran penegakan hukum TPPU yang kini menjadi bersifat multi-investigators. Tugas dan kewenangan penyidikan TPPU yang diatur dalam UU PPTPPU kini juga diberikan kepada seluruh penyidik tindak pidana asal (termasuk PPNS). Artikel ini merekomendasikan agar pembenahan PPNS perlu terus diupayakan agar kuantitas, kualitas dan profesionalitas PPNS terus meningkat, sehingga dapat melaksanakan fungsi penegakan hukum TPPU secara efektif.